Selective epoxidation of methyl soyate over alumina-supported group VI metal oxide catalysts - Satyarthi, Jitendra K.; Srinivas, D. (Applied Catalysis A-General, 2011)
Epoxidation of methyl soyate (biodiesel), soybean oil and oleic acid with tert.-butyl hydroperoxide (TBHP) was investigated over gamma-alumina-supported group VI metal oxides (CrOx/Al2O3, MoOx/Al2O3 and WOx/Al2O3) prepared by impregnation method. The studies revealed that 15 wt% MoOx on gamma-Al2O3 was the most active catalyst (conversion >90 mol% under optimized conditions). While MoOx/Al2O3 is selective mainly for epoxidation, the other catalysts are active for epoxidation as well as for decomposition of TBHP. The active species on the catalyst surface were investigated using in situ UV-visible spectroscopy. A linear correlation was observed between epoxidation activity and surface acidity of the catalyst. A new H-1 NMR method was developed to monitor the progress of epoxidation reaction which was found to be superior to gas chromatographic method in estimating the conversion of double bonds of fatty compounds. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Alumina-supported group VI metal oxides; Biodiesel; epoxidation; Fatty acids; H-1 NMR spectroscopy; MoOx/Al2O3; Vegetable oil

Catalytic decarboxylation of non-edible oils over three-dimensional, mesoporous silica-supported Pd - Raut, Ravindra; Banakar, Vikram V.; Darbha, Srinivas (Journal of Molecular Catalysis A-Chemical, 2016)
Deoxygenation of fatty acids (oleic and stearic acids) and non-edible oil (jatropha oil) over Pd(1-5 wt%) supported on two structurally different, three-dimensional, mesoporous silica (SBA-12 and SBA-16) catalysts was investigated. Pd/SBA-16 (cubic mesoporous structure with space group Im (3) over barm) showed higher catalytic activity than Pd/SBA-12 (hexagonal mesoporous structure with space group p6(3)/mmc). The influence of reaction parameters like temperature, H-2 pressure and Pd content as well as the nature of the feedstock on catalytic activity and product selectivity was studied. A temperature of above 320 degrees C, reaction time of 5 h and Pd content (on silica surface) of 3 wt% enabled complete conversion of the fatty compounds into diesel-range hydrocarbons. Deoxygenation proceeded through hydrodeoxygenation and decarboxylation mechanisms when a saturated (stearic) acid was used as a feed while it advanced mainly through decarboxylation route when an unsaturated (oleic) acid was employed. Higher surface hydrophobicity and smaller size particles of Pd are the possible causes for the superior catalytic activity of Pd/SBA-16. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Biofuel; Deoxygenation; Diesel-range hydrocarbons; Mesoporous silica; Supported palladium; Vegetable oil